@grogest_Ambiental: A Web-based Decision Support System for agribusiness - Feijó, Thiago; David, José Maria; Braga, Regina; Otenio, Marcelo Henrique; Paula, Vanessa R.; Santos, Gabriele Medeiros; Campos, Fernanda; Ströele, Victor (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2021)
In agribusiness, the treatment and sustainable management of waste in intensive production systems must consider productivity and economic gains in the short term and the sustainability of agricultural production. The acquisition of technical information, and the knowledge about the characteristics of the rural property, are fundamental for stakeholders, especially considering the adequacy of sustainable environmental practices. It is necessary to provide a web-based system to support stakeholders in discovering and understanding their productive context. This paper proposes a solution to support stakeholders' decision-making to improve sustainable practices in agribusiness. The proposed solution is applied in the agricultural domain, focusing on sustainability, by implementing a web system supported by an ontology to organize and provide strategic information through a mobile app. Technical and regulatory environmental practices documents are recommended for a relevant context, considering a feasibility study with experts in the field. As a result, the approach provided decision-making support offering technical information efficiently and agile for stakeholders.